Architectures of the Uncertainty: Narrative Structures in the Short Stories “Un sueño realizado” by J.C. Onetti, and “Amor a la distancia” by E. Paz Soldán - Breusa, Luca (2023)
The first half of the 20th century introduced the idea of the uncertainty in the scientific fields as well as in the art. Knowledge and creation were affected by the centrality assumed by the concept of uncertainty. It is possible to identify a specific literary field concerning uncertainty. Most novels and short stories belonging to the fantastic genre moves on the blurry limits between imagination and reality, that is to say between the condition of verosimilitude and impossibility of the narrative world. The postmodern fictions are structured in the sameway, exploring the blurry limits between fiction and reality according to the metafiction typical features. For this reason, the literature of uncertainty includes fantastic literature as well as postmodern one. In these fields of literature, all kinds of novels and short stories need an internal and low visible narrative structure. In my opinion the comparison between Juan Carlos Onetti’s “Un sueño realizado” and Edmundo Paz Soldán’s “Amor a la distancia” shows two different narrative models. Onetti’s short story, “Un sueño realizado”, could be an example of a static architecture of uncertainty built by assimilation. Otherwise, Paz Soldán’s short story, “Amor ala distancia”, could reveal a dynamic architecture of uncertainty made by alternation.